PELATIHAN KEWIRAUSAHAAN DAN AKUNTANSI DASAR BAGI ANAK DI DUSUN LAMPER MELALUI USAHA GELANG MANIK-MANIK - Sang Ayu Putu Astriani; Ni Nyoman Ernita Ratnadewi; I Putu Pasek Bagiartha W.; I Komang Widya Purnama Yasa (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service activity aims to improve children's understanding of entrepreneurship and basic accounting through the practice of making beaded bracelets in Lamper Hamlet, Jagaraga Village, Kuripan District, West Lombok Regency. The problem raised is the low level of entrepreneurial literacy and financial record-keeping among elementary and secondary school-aged children. In fact, instilling entrepreneurial values and financial management from an early age is important for developing creative, independent, and responsible characters. The method used is descriptive participatory, with an educational approach that involves providing materials, direct practice, and evaluation through questions and answers. The activity was held on July 9, 2025, involving 19 children as participants. The results of the activity showed that the children began to understand the concept of small businesses, the importance of recording income and expenses, and were able to apply these through a beaded bracelet business. They also demonstrated increased creativity, courage to express ideas, and enthusiasm for simple entrepreneurship. Evaluation through questions and answers proved that the visual and practical approach used was able to improve participants' understanding according to their age. This activity makes a positive contribution to improving children's entrepreneurial and financial literacy and has the potential to be further developed as a creative education model in rural communities.